Measurement of Co-Circulation of Currencies - Krueger, Russell (IMF Working Papers; Working Paper ;, 1995)
'Co-circulation' involves the regular use of two or more currencies within an economy. This paper examines methodologies to measure the extent to which foreign currencies are circulated within an economy. Ample anecdotal evidence exists that the U.S. dollar, DM, and other currencies are widely used outside their home countries, as general mediums of exchange, as speculative instruments, or as means of saving. Co-circulation is rarely estimated, which can result in serious errors in statistical estimates of international capital flows and monetary aggregates. We examine a variety of measurement techniques that might be used in various situations. However, estimation remains difficult or impossible in some settings. Limited evidence available suggests that co-circulation is widespread and large scale in some countries. In the final section, we discuss some policy implications of co-circulation regarding seigniorage, inflation control, and the partial integration of monetary systems that accompanies co-circulation. An appendix by Roman Zytek discusses possible sampling biases in measuring co-circulation due to segmentation in markets.